Problem-based learning model: Can it improve learning outcomes for long serve in badminton? - Suryadi, Didi; Samodra, Y Touvan Juni; Gustian, Uray; Yosika, Ghana Firsta; Sastaman B, Putra; Dewintha, Rezza; Saputra, Eko (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
This study aims to prove the improvement of learning outcomes from long service techniques in badminton games through problem-based learning models. The type of study used is the classroom action research design. The subjects of this study were students of Senior High School 2 Sukadana in the 2021–2022 school year, especially class X IPA students, totaling 25 students. The results showed an increase in cycle I, namely 28% completion, but there were still many students who were not complete, with a percentage of 72%. Based on the results in cycle II, it shows that there is a difference in the percentage achieved, namely, in cycle I, 28% of students are complete, and the last in cycle II shows a percentage of 92% of students are complete on the learning outcomes of the badminton long serve. The conclusion proves that the problem-based learning model can improve long-term service skills in badminton games. This research has provided new references related to physical education learning, where these results recommend that the problem-based learning model can be applied to solve badminton long serve problems.